TGFβ signaling sensitizes MEKi-resistant human melanoma to targeted therapy-induced apoptosis - Benjamin Loos; Adrian Salas-Bastos; Anna Nordin; Julien Debbache; Salome Stierli; Phil F. Cheng; Stefanie Rufli; Conrad Wyss; Mitchell P. Levesque; Reinhard Dummer; Wendy Wei-Lynn Wong; Steve Pascolo; et al. (Cell Death and Disease)
Abstract The TGFβ signaling pathway is known for its pleiotropic functions in a plethora of biological processes. In melanoma, TGFβ signaling promotes invasiveness and metastasis formation. However, its involvement in the response to therapy is controversial. While several studies have linked TGFβ signaling to elevated resistance to targeted therapy in melanoma, separate findings have indicated a favorable treatment response through TGFβ-mediated increase of cell death. We now found that the outcome of TGFβ signaling in the context of targeted therapy is dose dependent. Unlike low doses, high levels of TGFβ signal activation induce apoptosis upon simultaneous MAPK pathway inhibition, even in targeted therapy resistant melanoma cell lines. Using transcriptomic analyses, combined with genomic target identification of the critical TGFβ signaling effector SMAD4, we demonstrate that parallel activation of TGFβ signaling and MAPK pathway inhibition causes a complete switch of TGFβ target genes from promoting pro-invasive processes to fueling pro-apoptotic pathways. Investigations of underlying mechanisms identified a novel apoptosis-inducing gene signature. Functional validation of signature members highlighted a central role of the pro-apoptotic BCL2 family member BCL2L11 (BIM) in mediating apoptosis in this condition. Using a modified, synthetic version of the TGFB1 mRNA for intra-tumoral injections, we additionally showcase a potential therapeutic application of this treatment combination.